Maize Seed Quality Evaluation at the Temperature Room Storage with Open Package Condition - Rahmawati Rahmawati; Suwarti Suwarti; M. Aqil (AGRIVITA, Journal of Agricultural Science, 2019)
Traditional farmers do seeds storage simply by putting it on the floor of their home without a specific treatment. The seed quality testing carried out in several varieties was stored at room temperature with open packaging condition to determine the viability and vigor. The experiment was conducted in ICERI, Maros, South Sulawesi from May 2014 to January 2015. Research was arranged in a randomized complete design with four replications. Seeds were taken from ICERI seed storage warehouse. Furthermore, seeds were stored in temperature room with an open packaging condition. Parameter observations conducted on moisture content of seed, 1000-grain weight, electrical conductivity, germination, growth rate, primer root length and shoot length. Stored period of seeds in an open package at room temperature shelf life was strongly influenced by previous seed storage and seed weight of current variety. Seed that had long been stored in storage shed and small seed weight would accelerate the decline of physiological seed quality, especially growth rate and percentage of germination. Storage of seeds in an open package at room temperature could maintain quality of the seeds up to 3 months with large grain weight on the varieties and the low water content of the initial storage.